Case Report: Imaging features of a new type double inferior vena cava malformation and review - Wu, Yu-lin; Yang, Guo-kai; Chen, Qian; Tang, Yi; Zhang, Jian-hui; Wu, Shao-jie; Cai, Sen-lin; Zhou, Yan-feng; Zhu, Yao-Bin; Luo, Jie-wei; Fang, Zhu-ting (Frontiers in Cardiovascular Medicine, 2023)
Background Double inferior vena cava (DIVC) is a rare vascular malformation. With advances in radiological techniques and diagnosis, more and more types of DIVC were identified and diagnosed. Recognition of the variety of DIVC seen on imaging is essential for subsequent venous interventions. Case presentation A 77-year-old man presented with low back pain with left lower limb pain for 1 month. Scattered petechiae above the skin surface on the left lower leg, especially on the extensor surface, with flaking and mild tingling of the skin, were noted 3 weeks ago. Ultrasound revealed deep vein thrombosis (DVT) in the left lower limb. Computed tomography pulmonary angiography (CTPA) suggested no significant thrombus in the pulmonary artery. Computed tomography venography (CTV) of bilateral lower limbs showed that iliac vein compression syndrome with formation of deep and superficial venous traffic branches in bilateral lower limbs, predominantly on the left side. CTV of the inferior vena cava (IVC) suggested that the left common iliac vein crossed the common iliac artery bifurcation from dorsal to ventral and continued to travel cranially as a ventral vessel, and connected with the ventral IVC anterior to the right common iliac artery. The right common iliac vein extended cephalad as a dorsal vessel, which was narrowed at the level of 4th lumbar vertebra by compression of the hyperplastic bone and the osteophyte. The patient was discharged after right and left common iliac vein angiography and balloon dilation of bilateral common iliac vein. Conclusion The formation of both ventrally and dorsally aligned DIVC is rarer. It should be clarified the effects of DIVC on DVT formation, and the importance of imaging for preoperative planning.